Tidal and subtidal exchange flows at an inlet of the Wadden Sea. (5th March 2018) - Valle-Levinson, Arnoldo; Stanev, Emil; Badewien, Thomas H.
Abstract: Observations of underway velocity profiles during complete spring and neap tidal cycles were used to determine whether the spatial structures of tidal and subtidal flows at a tidal inlet in a multiple-inlet embayment are consistent with those observed at single-inlet embayments. Measurements were obtained at the Otzumer Balje, one of the multiple inlets among the East Frisian Islands of the Wadden Sea. The 1.5 km-wide inlet displayed a bathymetric profile consisting of a channel ∼15 m deep flanked by <5 m shoals. Neap tide observations spanned 36 h in the period May 11–12, 2011, while spring tide measurements exceeded 48 h from May 17 to May 19, 2011. Analysis of observations indicate that frictional effects from bathymetry molded tidal flows. Spatial distributions of semidiurnal tidal current amplitude and phase conform to those predicted by an analytical model for a basin with one inlet. Maximum semidiurnal flows appear at the surface in the channel, furthest away from bottom friction effects. Therefore, Otzumer Balje displays tidal hydrodynamics that are independent of the other inlets of the embayment. Subtidal exchange flows are laterally sheared, with residual inflow in the channel combined with outflow over shoals. The spatial distribution of these residual flows follow theoretical expectations of tidally driven flows interacting with bathymetry. Such distribution is similar to the tidal residual circulation at other inlets with only one communication to the ocean, suggesting that at subtidal scales the Otzumer Balje responds to tidal forcing independently of the other inlets.